2011
DOI: 10.1186/1471-2229-11-125
|View full text |Cite
|
Sign up to set email alerts
|

Localization of DIR1 at the tissue, cellular and subcellular levels during Systemic Acquired Resistance in Arabidopsisusing DIR1:GUS and DIR1:EGFP reporters

Abstract: BackgroundSystemic Acquired Resistance (SAR) is an induced resistance response to pathogens, characterized by the translocation of a long-distance signal from induced leaves to distant tissues to prime them for increased resistance to future infection. DEFECTIVE in INDUCED RESISTANCE 1 (DIR1) has been hypothesized to chaperone a small signaling molecule to distant tissues during SAR in Arabidopsis.ResultsDIR1 promoter:DIR1-GUS/dir1-1 lines were constructed to examine DIR1 expression. DIR1 is expressed in seedl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 79 publications
5
32
0
Order By: Relevance
“…1e), as previously reported 12,34,35 . AZI1:GFP was present in the microsomal and chloroplast fractions, but was not detected in soluble and apoplastic fractions (Fig.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…1e), as previously reported 12,34,35 . AZI1:GFP was present in the microsomal and chloroplast fractions, but was not detected in soluble and apoplastic fractions (Fig.…”
Section: Resultssupporting
confidence: 81%
“…To obtain apoplast extracts (intercellular washing fluid) 34 from N. benthamiana: fully expanded leaves of 4-week-old plants infiltrated with Agrobacterium harbouring the different constructs were vacuum infiltrated with sterile distilled water and leaf surfaces dried with absorbent paper before collection of the intercellular washing fluid. To collect the intercellular washing fluid, leaves were centrifuged in swinging buckets at 300 g for 15 min at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Previously we hypothesized that DIR1 moves to distant tissues during SAR (Maldonado et al, 2002) and recently demonstrated that DIR1 is well situated to participate in long distance signaling as it is expressed in companion cells and sieve elements (Champigny et al, 2011). Numerous reviews (Durrant and Dong, 2004; Parker, 2009; Dempsey and Klessig, 2012) present models in which DIR1 translocates to distant tissues during SAR.…”
Section: Introductionmentioning
confidence: 99%
“…Expression and localization of DIR1 using DIR1pro:GUS and DIR1 pro:DIR1-GUS fusion lines (Champigny et al, 2011) demonstrated that DIR1 is expressed in seedlings and flowers, and ubiquitously in untreated or mock-inoculated mature leaf cells including phloem sieve elements and companion cells. Intercellular washing fluid (IWF) experiments and subcellular localization of transiently expressed DIR1:EGFP in tobacco indicated that DIR1's ER signal sequence targets it for secretion to the cell wall.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation